Development of photocatalysts based on TiO2 films with embedded Ag nanoparticles. (27th March 2022) - Roldán, María Virginia; Porta, Estanislao; Durán, Alicia; Castro, Yolanda; Pellegri, Nora
Abstract: In this work, the synthesis, characterization, and study of the photocatalytic activity of polycrystalline TiO2 coatings with embedded Ag nanoparticles (Ag‐TiO2 ) were presented. In particular, the TiO2 and Ag‐TiO2 coatings were developed using a simple and improved sol‐gel technique. Very stable TiO2 sols containing Ag nanoparticles were prepared and deposited by dip‐coating process onto glass substrates obtaining homogeneous and transparent thin films. The well‐distribution of silver nanoparticles into the TiO2 sol allows TiO2 coatings with Ag nanoparticles distributed throughout the volume of the material to be obtained. A significant improvement of the photocatalytic activity was observed for the Ag‐TiO2 coatings. The photocatalytic mechanism implicated in the dye degradation (methyl orange) by hydroxyl (OH) and superoxide (O2 – ) radicals was studied using several scavengers. Thus, it is concluded that the addition of Ag nanoparticles does not modify the mechanisms involved in the dye degradation, evidencing the good stability of the photocatalyst.